Fabrication of composite polymer electrolyte membrane using acidic metal-organic frameworks-functionalized halloysite nanotubes modified chitosan. (4th June 2021) - Zhao, Shujun; Yang, Yutong; Zhong, Fei; Niu, Wenjuan; Liu, Yingshui; Zheng, Genwen; Liu, Hai; Wang, Jie; Xiao, Zufeng
Abstract: For the purpose of preparing high performance proton exchange membrane (PEM) with combined low cost and high selectivity, SO3 H-UiO-66 coated halloysite nanotubes (SO3 H-UiO-66@HNTs) was prepared by a facile one-pot in situ growth method, and then was employed as a multifuctional addtive into chitosan (CS) matrix to fabricate composite PEM. The coating of SO3 H-UiO-66 provides SO3 H-UiO-66@HNTs with satisfying compatibility and dispersibility with CS matrix. As a result, SO3 H-UiO-66@HNTs dispersed homogeneously within CS matrix and thus composite membrane dispalys improved mechanical strength and methonal resistance. Incorporating 10 wt% of SO3 H-UiO-66@HNTs into CS matrix results in 0.73-fold increased mechanical strength and 0.54-fold decreased methonal crossover. Due to the embedding of hierarchical core-shell nanobybrid comprising of one-dimensional halloysite nanotubes and a stable MOF with abundant functional –SO3 H groups, composite membranes not only enhanced water absorpotion ability, which facilitates the formation of internal interconnected water networks for faster proton transfer, but also obtains additional proton-hoping sites and new channel-like proton-conducting pathway along CS–SO3 H–UiO-66@HNTs interface, which is of benefit to the de-protonation/protonation procedure. CS/SO3 H-UiO-66@HNTs-10 composite membrane obtains conductivity of 46.2 mS cm −1 (80 °C) and maximum power density of 84.5 mW cm −2 (70 °C), which are respectively 57.6% and 77.1% higher than the pristine CS membrane. Moreover, the durability test further proves the satisfactory stability of CS/SO3 H-UiO-66@HNTs-10 composite membrane. Graphical abstract: Image 1 Highlights: MoS2 @CNTs with a hierarchical nanostructure consisting of one-dimensional CNTs and two-dimensional MoS2 nanosheets were prepared using in-situ growth method. MoS2 @CNTs was incorporated into SPEEK matrix to prepare composite membranes. Resulting membranes have high conductivity, strength and low methanol perme ability. The DMFC peak power density of 98.5 mW cm −2 at 70 o C was obtained. The composite membranes provide significant prospect as a promising proton exchange membrane for DMFC application.